2008
DOI: 10.2193/2007-513
|View full text |Cite
|
Sign up to set email alerts
|

Waterfowl Nesting in Fall‐Seeded and Spring‐Seeded Cropland in Saskatchewan

Abstract: Waterfowl nesting in annual croplands has remained a little‐known aspect of waterfowl nesting ecology because of the inability of many studies to systematically search this habitat through the nesting season. Where searches have been conducted, they are generally restricted to the period prior to seeding, and many nests found are destroyed by the seeding operation. Consequently, fall‐seeded crops have been promoted as an alternative cropping practice that could increase nest survival of waterfowl nesting in cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 19 publications
(32 reference statements)
5
60
0
Order By: Relevance
“…Nest survival of ducks in spring-seeded cropland is low compared to most other habitat types (Klett et al 1988, Greenwood et al 1995), ranging from < 1-4% (Richkus 2002), 2% (Greenwood et al 1995), and 7% (Klett et al 1988). Devries et al (2008a) reported a relatively high nest success rate of 12% in spring-seeded cropland and opined that this may have been a result of their inclusion of late-season nests because success rates in spring-seeded cropland can increase substantially throughout the growing season (Emery et al 2005). Recently, one of us (JHD) modeled mean pintail nest success in spring-seeded cropland to be 5.1% (i.e., daily survival rate = 0.9111 + 0.0146; Table 2) based on the fate of 153 nests in cropland (Devries et al 2018).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nest survival of ducks in spring-seeded cropland is low compared to most other habitat types (Klett et al 1988, Greenwood et al 1995), ranging from < 1-4% (Richkus 2002), 2% (Greenwood et al 1995), and 7% (Klett et al 1988). Devries et al (2008a) reported a relatively high nest success rate of 12% in spring-seeded cropland and opined that this may have been a result of their inclusion of late-season nests because success rates in spring-seeded cropland can increase substantially throughout the growing season (Emery et al 2005). Recently, one of us (JHD) modeled mean pintail nest success in spring-seeded cropland to be 5.1% (i.e., daily survival rate = 0.9111 + 0.0146; Table 2) based on the fate of 153 nests in cropland (Devries et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…More contemporary studies from prairie Canada have found that predation is the predominant cause of duck nest loss in cropland rather than farming operations. Greenwood et al (1995) and Devries et al (2008a) reported that 17% and 22%, respectively, of nests of various duck species in cropland (primarily spring-seeded) in prairie Canada were lost to agricultural activity. Pintail nest loss from agricultural practices in spring-seeded cropland estimated from various sources averages 21.8% (+ 1.3%; Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, pintails and their nests may be more vulnerable to spring seeding activities than other species of prairie ducks, leading to reduced nest success and overall productivity (Hestbeck 1995, Miller and Duncan 1999, Podruzny et al 2002, Hebert and Wassenaar 2005. However, there are indications that widespread use of fall-seeded crops in Prairie Canada could improve nest success and the abundance of pintails (Devries et al 2008, Skone et al 2016). …”
Section: Discussionmentioning
confidence: 99%